2014
DOI: 10.3390/md12021043
|View full text |Cite
|
Sign up to set email alerts
|

Co-Cultivation—A Powerful Emerging Tool for Enhancing the Chemical Diversity of Microorganisms

Abstract: Marine-derived bacteria and fungi are promising sources of novel bioactive compounds that are important for drug discovery programs. However, as encountered in terrestrial microorganisms there is a high rate of redundancy that results in the frequent re-discovery of known compounds. Apparently only a part of the biosynthetic genes that are harbored by fungi and bacteria are transcribed under routine laboratory conditions which involve cultivation of axenic microbial strains. Many biosynthetic genes remain sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
215
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(223 citation statements)
references
References 88 publications
(152 reference statements)
4
215
0
4
Order By: Relevance
“…Here, the simple and previously successful one-strain-many-active-compounds (OSMAC) approach may be used which aims to activate metabolic pathways to produce different types of metabolites in order to identify the range of compounds that may be produced by a specific bacterial isolate [58]. The use of different fermentation nutrients and parameters as well as co-culturing of competing or antagonistic microorganisms may aid in the search for important active metabolites that may be used as antimicrobial or anticancer agents [34,59]. A study carried out by Graça et al (2015) reported that the use of liquid fermentation, the same technique used in this study, over solid media fermentation to obtain antimicrobial extracts is advantageous in its ability to be quantitative, simple, quick to carry out, reproducible, less expensive than other methods used and able to be conducted in a high throughput way [8].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the simple and previously successful one-strain-many-active-compounds (OSMAC) approach may be used which aims to activate metabolic pathways to produce different types of metabolites in order to identify the range of compounds that may be produced by a specific bacterial isolate [58]. The use of different fermentation nutrients and parameters as well as co-culturing of competing or antagonistic microorganisms may aid in the search for important active metabolites that may be used as antimicrobial or anticancer agents [34,59]. A study carried out by Graça et al (2015) reported that the use of liquid fermentation, the same technique used in this study, over solid media fermentation to obtain antimicrobial extracts is advantageous in its ability to be quantitative, simple, quick to carry out, reproducible, less expensive than other methods used and able to be conducted in a high throughput way [8].…”
Section: Discussionmentioning
confidence: 99%
“…2B). For many more examples of mixed fermentation, we refer the reader to two comprehensive reviews by Pettit and Proksch (Pettit 2009;Marmann et al 2014).…”
Section: Application: Cell-cell Contactmentioning
confidence: 99%
“…Overall, the roles of NPs in mediating antagonistic, mutualistic, or exploitative associations among microbial populations has significant implications for their distribution in the environment, and suggests testable hypotheses with significant potential to inform NP discovery efforts. For example, the prevalence of sympatric inhibitory and signaling interactions suggests that efforts to co-culture isolates to activate silent BGCs [7,59,100] should focus on sympatric isolates that share a co-evolutionary history. Moreover, in cases where cooperative interactions occur, molecules from sympatric isolates may be hypothesized to be more likely to have synergistic activities.…”
Section: Roles Of Nps In Biotic Interactionsmentioning
confidence: 99%